2009
DOI: 10.4049/jimmunol.0801599
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 Is a Negative Regulator of Th17 Cells and Tissue Pathology in a Pulmonary Model of Fungal Infection

Abstract: To study the role of TLR2 in a experimental model of chronic pulmonary infection, TLR2-deficient and wild-type mice were intratracheally infected with Paracoccidioides brasiliensis, a primary fungal pathogen. Compared with control, TLR2−/− mice developed a less severe pulmonary infection and decreased NO synthesis. Equivalent results were detected with in vitro-infected macrophages. Unexpectedly, despite the differences in fungal loads both mouse strains showed equivalent survival times and severe pulmonary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
135
2
18

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(166 citation statements)
references
References 60 publications
11
135
2
18
Order By: Relevance
“…However, the regulatory effects of TLR2 on Th17 cells have appeared to be contradictory in various studies. In pulmonary fungal infection and brain abscess, TLR2 was reported to act as a negative regulator for Th17 cells (24,37), whereas in experimental autoimmune encephalomyelitis, skin inflammation, and tuberculosis infection, TLR2 was reported to have the opposite effect (38)(39)(40). These findings suggest that the specific effect of TLR2 on Th17 cells varies with the type of immune response and depends on the microenvironment of the target tissues.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, the regulatory effects of TLR2 on Th17 cells have appeared to be contradictory in various studies. In pulmonary fungal infection and brain abscess, TLR2 was reported to act as a negative regulator for Th17 cells (24,37), whereas in experimental autoimmune encephalomyelitis, skin inflammation, and tuberculosis infection, TLR2 was reported to have the opposite effect (38)(39)(40). These findings suggest that the specific effect of TLR2 on Th17 cells varies with the type of immune response and depends on the microenvironment of the target tissues.…”
Section: Discussionmentioning
confidence: 65%
“…In several in vivo studies, TLR2 has been demonstrated to control the expansion and function of T reg cells (21)(22)(23), which inhibit Th17 cells via TLR2 signals in a pulmonary fungal infection model system (24). These findings led us to hypothesize that the TLR2-dependent expansion of T reg cells might inhibit Th17 cells in the BIPF model.…”
Section: Tlr2-dependent T Reg Cells Have Minimal Inhibitory Effect Onmentioning
confidence: 98%
“…In a murine model of S. aureus brain abscess, TLR2 deficiency was associated with the increased infiltration of IL-17 producing T cells to the lesions [24]. Similarly, in Paracoccidioides brasiliensis infection of the lung, TLR2 À/À mice displayed a Th17 phenotype that was associated with impaired expansion of regulatory CD4 1 CD25 1 Foxp3 1 T cells [25]. In contrast, the TLR2 ligand Pam 3 CSK 4 was shown to directly induce the production of IL-17 by gdT cells [26].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, TLR2 engagement was shown to favor Th2 responses in some cases (19), to promote IFN-␥ production in other studies (20), and has been shown to promote IL-10 production and enhance Treg activity in vivo (21). TLR2 has been shown to also regulate IL-17 production; however, different infection models have shown either enhancing (22,23) or inhibitory effects (24,25), and its direct effect on IL-17 production by Ag-specific T cells is not clear. Therefore, the role of TLR2 engagement in driving the differentiation of CD4 T cells during priming in vivo remains an unresolved issue.…”
Section: Tlr2 Engagement On Dendritic Cells Promotes Highmentioning
confidence: 93%
“…TLR2 expression was also found to promote IL-17 production in human CD4 T cells (22), consistent with our results here. However, in infection models, TLR2 deficiency has been associated with increased IL-17 production in inflammatory sites (24,25), suggesting that other influences of inflammation and infection may affect how different TLR control T cell responses. TLR2 engagement has also been associated with increased Treg expansion in vivo (20,33,46,54), although this TLR2-mediated effect was due to direct ligation of TLR2 on Tregs (20,33).…”
Section: Discussionmentioning
confidence: 99%